Under-reporting of Parkinson's disease on death certificates: A population-based study (NEDICES) - Benito-León, Julián; Louis, Elan D.; Villarejo-Galende, Alberto; Romero, Juan Pablo; Bermejo-Pareja, Félix (Journal of the neurological sciences, 2014)
Parkinson's disease is frequently omitted as a cause of death from death certificates. A limitation of previous studies that attempted to assess the validity of death certificates is that population-dwelling cases, with milder, undiagnosed Parkinson's disease were likely excluded. As a result, those studies likely overestimated the validity of death certificates because they did not include these milder cases. We assessed the validity of death certificates in a prospective population-based study (NEDICES), which includes previously undiagnosed Parkinson's disease cases detected during the assessment. 3926 community-dwelling elderly subjects with and without Parkinson's disease were followed during a median of 12.6years, after which the death certificates of those who died were examined. We calculated the proportion of cases of clinically diagnosed Parkinson's disease for whom a diagnosis of Parkinson's disease was certified as the basic cause of death on death certificates. 1791 (45.6%) of the 3926 participants died over a median follow-up of 7.1years, including 82 (73.9%) deaths among 111 participants with Parkinson's disease. Parkinson's disease was rarely certified as the basic cause of death (14.6%). Gender, disease stage and the period during which the study was conducted (i.e., 1994 to 2007) did not influence the likelihood that Parkinson's disease would be reported. Our findings reinforce the notion that the reporting of Parkinson's disease on death certificates remains poor. This suggests a lack of awareness of the importance of Parkinson's disease as a cause of death. •In this population-based study, PD was reported in less than one-fifth of the certificates.•Reporting of PD on death certificates remains poor.•PD should be considered as a risk factor for increased mortality in the elderly.